Translation Techniques of Refusal Strategies in Indonesian Novel `Kekejian Yang Indah` Translated from English Novel `The Beautiful Malice` - Wyut Yee Soe; M. R. Nababan; Djatmika Djatmika (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
This study is about the analysis of English refusal strategies and their translation in Indonesian as found in the novel entitled Kekejian Yang Indah. The aims of the study are to find out the types of refusal strategies in the original novel and to identify the translation techniques applied by the translator to translate the refusal strategies into Indonesian. The linguistic data were analyzed by using the theory of refusal strategies proposed by Beebe et al (1990). Meanwhile, the translation techniques were identified based on Molina and Albir (2002). The result shows that there are 91 data of refusal strategies. There are 67 direct refusal strategies and 24 indirect refusal strategies. The direct refusal strategies are translated by using established equivalent (135 data), modulation (22 data), explicitation (19data), variation (19 data), implicitation (14 data), pure borrowing (6 data), reduction (5 data), addition (5 data), deletion (4 data), transposition (2 data), adaptation (1 data), paraphrase (1 data) and discursive creation (1 data). Meanwhile, the indirect refusal strategies are translated by applying established equivalent (49 data), variation (16 data), explicitation (10 data), modulation (8 data), addition (4 data), pure borrowing (3 data), reduction (2 data) and paraphrase (1 data). By using established equivalent frequently, it is assumed that translation of refusal strategies in `Kekejian yang Indah` reflects familiar and usual translation.